(untitled) (Global Journal of Human-Social Science, 2023)
The fast-evolving scenario of the global economy of the past few decades has contributed to the transformation of cities into prime economic hubs providing sustenance for the growing urban populace In keeping pace with economic development and subsequent demand for shelter cities are densifying through vertical expansion to avoid urban sprawl Given the rapid urbanization along with the scarcity of developable urban land open spaces have become a highly contested commodity particularly in the residential of the Dhaka megacity Driven by the profit-maximizing agenda of the developers the ongoing process of residential densification is exacerbating the situation Urban densification of Dhaka is faced with the challenge in keeping the residential areas sustainable and environmentally friendly This study attempts to investigate the impact of the densification process on the spatial quality of the residential built environment of Dhaka through the lens of environmental sustainability The explorative research was conducted through a questionnaire survey informal interviews and field survey across seven residential areas of Dhaka undergoing the densification process